Association between exposure to air pollution and late-life neurodegenerative disorders: An umbrella review - LeeAnn Tan (Elsevier, 2022)
Summary: There is growing concern regarding air pollution as a modifiable risk factor for cognitive impairment, dementia, Alzheimer’s disease, and Parkinson’s disease. We conducted an umbrella review to collate the available evidence from systematic reviews and meta-analyses investigating the association between exposure to air pollution and risk of late-life neurodegenerative disorders. A narrative overview and visual summary of the findings from both quantitative and qualitative reviews are presented. A range of air pollutants were assessed in the included meta-analyses; however, only exposure to fine particulate matter (PM2·5) was significantly associated with increased risk of cognitive impairment and Alzheimer’s disease. Although associations between exposure to air pollution and late-life neurodegenerative disorders are frequently reported at the individual study level, as seen in the qualitative summary of findings, attempts to quantitatively synthesise these findings generally resulted in suggestive support for the strength of the associations. Over- or underestimation of effect size is possible in view of the wide variation in methodologies used across individual studies. Recommendations for improvements in design, analysis, and reporting as summarised in the present review should be considered when planning future studies to increase the consistency, comparability, and utility of their findings.